Pectic enzymes as potential enhancers of ascorbic acid production through the D-galacturonate pathway in Solanaceae. (January 2018) - Rigano, Maria Manuela; Lionetti, Vincenzo; Raiola, Assunta; Bellincampi, Daniela; Barone, Amalia
Graphical abstract: Highlights: The tomato introgression line IL12-4-SL has high levels of ascorbate in the fruit. Genes coding for pectic enzymes were identified in the introgressed region 12-4-SL. The identified pectic enzymes affect theD -galacturonate pathway in tomato fruits. There is a correlation between pectic enzymes activity and ascorbic acid content. Pectic enzymes enhance ascorbate production in Solanaceae. Abstract: The increase ofL -Ascorbic Acid (AsA) content in tomato ( Solanum lycopersicum ) is a common goal in breeding programs due to its beneficial effect on human health. To shed light into the regulation of fruit AsA content, we exploited a Solanum pennellii introgression line (IL12-4-SL) harbouring one quantitative trait locus that increases the content of total AsA in the fruit. Biochemical and transcriptomic analyses were carried out in fruits of IL12-4-SL in comparison with the cultivated line M82 at different stages of ripening. AsA content was studied in relation with pectin methylesterase (PME) activity and the degree of pectin methylesterification (DME). Our results indicated that the increase of AsA content in IL12-4-SL fruits was related with pectin de-methylesterification/degradation. Specific PME, polygalacturonase (PG) and UDP-D -glucuronic-acid-4-epi mer ase (UGlcAE) isoforms were proposed as components of theD -galacturonate pathway leading to AsA biosynthesis. The relationship between AsA content and PME activity was also exploited in PMEI tobacco plants expressing a specific PME inhibitor (PMEI). Here we report that tobacco PMEI plants, altered in PME activity and degree of pectin methylesterification, showed a reduction in low methylesterified pectic domains and exhibited a reduced AsA content. Overall, our results provide novel biochemical and genetic traits for increasing antioxidant content by marker-assisted selection in the Solanaceae family.